The Steiner formula for Minkowski valuations - Parapatits, Lukas (Academic Press, 2012)
A Steiner type formula for continuous translation invariant Minkowski valuations is established. In combination with a recent result on the symmetry of rigid motion invariant homogeneous bivaluations, this new Steiner type formula is used to obtain a family of Brunn–Minkowski type inequalities for rigid motion intertwining Minkowski valuations.